Wind of Change? Cultural Determinants of Maternal Labor Supply - Barbara Boelmann; Anna Christina Raute; Uta Schönberg (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Does the culture in which a woman grows up influence her labor market decisions once she has had a child? And to what extent can exposure to a different cultural group in adulthood shape maternal labor supply? To address these questions, we exploit the setting of the German reunification. A state socialist country, East Germany strongly encouraged mothers to participate in the labor market full-time, whereas West Germany propagated a more traditional male breadwinner-model. After reunification, these two cultures were suddenly thrown together, with consequent increased social interactions between East and West Germans through migration and commuting. Zooming in on East and West Germans who migrated across the former inner-German border, we document a strong asymmetry in the persistence of the culture in which women were raised. Whereas East German female migrants return to work earlier and work longer hours than their West German colleagues even after long exposure to the more traditional West German culture, West German migrants adjust their post-birth labor supply behavior nearly entirely to that of their East German colleagues. West German return migrants continue to be influenced by the more gender egalitarian East German norm even after their return to the West, pointing towards the importance of learning from peers. Finally, taking advantage of differential inflows of East German migrants across West German workplaces in the aftermath of reunification, we show that even a partial exposure to East German colleagues induces “native” West German mothers to accelerate their return to work after childbirth, suggesting that migration might be a catalyst for cultural change.
Keywords: J10; J20; Z10; 330; cultural transmission; social norms; maternal labor force participation; German reunification